Reconocimiento de unidades del basamento proterozoico de las Sierras Septentrionales de la provincia de Buenos Aires en las estancias Cerro Blanco y La Torcaza a través del procesamiento de imágenes Sentinel - Benítez, Manuela E. (2017)
Recognition of Proterozoic basement units of the Sierras Septentrionales de la provincia de Buenos Aires at Cerro Blanco and La Torcaza farms by means of SENTINEL image processing. The use and processing of satellite images is a methodology that has been used for several years as a fundamental tool for location and first approach to the geological knowledge of a study area. In the present work, the application of the new SENTINEL 2A satellite images of high spatial resolution allowed recognizing unknown outcrops of Proterozoic basement in the area located to the North of Arroyo de los Huesos. Furthermore, it allowed discriminating different lithological types that were later characterized by field works and petrographic analysis. Among these types, the existence of a quartz rock body of geological features that has not been cited yet for the Sierras de Azul of Buenos Aires is highlighted. These new imagery would also contribute to other basement outcrop discoveries in the Tandilia System.